Pengembangan UI/UX Website Uluresto untuk Meningkatkan Efisiensi Operasional Restoran Menggunakan Metode Design Thinking - Putra, Anak Agung Adi Wiryya; Rada, I Nyoman Theo Ardiles (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2025)
Current technological developments have developed from year to year, where in the last few decades, technology has played an important role in driving progress in various fields. This study aims to design the UI/UX of a food ordering application for Uluresto MSMEs using the Design Thinking method. The type of research used is research and development. The sampling technique used is random sampling and 10 respondents were obtained. The results of the study show that users are satisfied with the experience of using the application. This application is able to provide intuitive, flexible, and satisfying interactions for Uluresto application users. Therefore, it can be concluded that the design being tested can be used well by research respondents. This can be seen from testing 10 respondents. With the SUS results assessed by users, the final result of SUS 85.25 is included in the fairly high points with that value. The Uluresto website design is in accordance with the quality desired by users. Further suggestions for further research include the addition of personalized recipe features according to the menu available at the restaurant concerned.